MR spectroscopy indicates diffuse multiple sclerosis activity during remission. Issue 12 (21st June 2009) - Kirov, I I; Patil, V; Babb, J S; Rusinek, H; Herbert, J; Gonen, O
Abstract : Objective: To test the hypothesis that diffuse abnormalities precede axonal damage and atrophy in the MRI normal-appearing tissue of relapsing-remitting (RR) multiple sclerosis (MS) patients, and that these processes continue during clinical remission. Methods: Twenty-one recently diagnosed mildly disabled (mean disease duration 2.3 years, mean Expanded Disability Status Scale score of 1.4) RR MS patients and 15 healthy matched controls were scanned with MRI and proton MR spectroscopic imaging ( 1 H-MRSI) at 3 T. Metabolite concentrations: N -acetylaspartate (NAA) for neuronal integrity; choline (Cho) for membrane turnover rate; creatine (Cr) and myo-inositol (mI) for glial status were obtained in a 360 cm 3 volume of interest (VOI) with 3D multivoxel 1 H-MRSI. They were converted into absolute amounts using phantom replacement and normalised into absolute concentrations by dividing by the VOI tissue volume fraction obtained from MRI segmentation. Results: The patients' mean VOI tissue volume fraction, 0.92 and NAA concentration, 9.6 mM, were not different from controls' 0.94 and 9.6 mM. In contrast, the patients' mean Cr, Cho and mI levels 7.7, 1.9 and 4.1 mM were 9%, 14% and 20%, higher than the controls' 7.1, 1.6 and 3.4 mM (p = 0.0097, 0.003 and 0.0023). Conclusions: The absence of early tissue atrophy and apparent axonal dysfunction (NAA loss) in these RR MS patients suggests that both are preceded by diffuse glial proliferation (astrogliosis), as well as possible inflammation, demyelination and remyelination reflected by elevated mI, Cho and Cr, even during clinical remission and despite immunomodulatory treatment.